2017
DOI: 10.1103/physrevx.7.021002
|View full text |Cite
|
Sign up to set email alerts
|

Brownian yet Non-Gaussian Diffusion: From Superstatistics to Subordination of Diffusing Diffusivities

Abstract: A growing number of biological, soft, and active matter systems are observed to exhibit normal diffusive dynamics with a linear growth of the mean-squared displacement, yet with a non-Gaussian distribution of increments. Based on the Chubinsky-Slater idea of a diffusing diffusivity, we here establish and analyze a minimal model framework of diffusion processes with fluctuating diffusivity. In particular, we demonstrate the equivalence of the diffusing diffusivity process with a superstatistical approach with a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
528
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 382 publications
(559 citation statements)
references
References 115 publications
(133 reference statements)
28
528
3
Order By: Relevance
“…Similarly, in simulations of crowded membranes it was shown that δ is between 1.3 and 1.6, and α below 1 [33] 4 . This behaviour can be explained by the fact that the considered medium is spatially or temporally heterogeneous [23,24,28,[35][36][37]. In such a system the thermal fluctuations are still Gaussian but the observed displacements are mixtures of these Gaussian contributions with random weights, effecting the non-Gaussian outcome.…”
Section: Physical Stochastic Modelling and Autoregressive Models 21mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in simulations of crowded membranes it was shown that δ is between 1.3 and 1.6, and α below 1 [33] 4 . This behaviour can be explained by the fact that the considered medium is spatially or temporally heterogeneous [23,24,28,[35][36][37]. In such a system the thermal fluctuations are still Gaussian but the observed displacements are mixtures of these Gaussian contributions with random weights, effecting the non-Gaussian outcome.…”
Section: Physical Stochastic Modelling and Autoregressive Models 21mentioning
confidence: 99%
“…X see [23][24][25][26][27] as well as the extensive list of references in [28]. These 'Brownian yet non-Gaussian' processes along with a more general class of non-Gaussian PDFs, discussed in more detail below, are in the focus of this study.…”
Section: Introductionmentioning
confidence: 99%
“…An interesting feature of this model, which is also observed in a variety of soft-matter and biological systems92425, is the long coexistence of a van Hove distribution with non gaussian tails, and of a mean square displacement linear in time. An important open question ahead concerns the temporal evolution of the van Hove distribution in the underdamped limit, to rationalize how normal diffusion is recovered.…”
Section: Discussionmentioning
confidence: 73%
“…In 2012 Chubynsky and Slater independently proposed a special case of the CIR process as a model of non-Gaussian diffusion [19,77]. This led the way to a wider range of models based on fluctuating diffusivity coefficient with a short time memory [78][79][80][81][82]. The evolution of the diffusion coefficient in the CIR model is defined by the stochastic equation , consequently D d 0 t > which causes the motion to stay positive.…”
Section: Diffusing-diffusivitymentioning
confidence: 99%
“…The CIR process for ab  Î , can be proved to be a sum of squared independent Ornstein-Uhlenbeck processes, which follows directly from writing the stochastic differential equation of such a sum [83]. Thus, a natural generalisation is to consider D t being a square of a Gaussian process [80,81]. We will assume that the velocity can be decomposed as…”
Section: Diffusing-diffusivitymentioning
confidence: 99%